Psychosocial needs of post-radiotherapy cancer survivors and their direct caregivers – a systematic review - Man, Ka Hei; Law, Helen Ka-Wai; Tam, Shing Yau (Frontiers in Oncology, 2023)
Radiotherapy is an important modality for cancer treatment. About 50% of cancer patients receive radiotherapy, and one-third of radiotherapy recipients were identified as having unmet psychosocial needs. The unmet psychosocial needs worsen the patient’s quality of life and treatment effectiveness. This review aims to identify the psychosocial needs of post-radiotherapy cancer survivors and their direct caregivers. Systematic research of Embase, Scopus and PubMed was done and 17 studies were selected for analysis. The results show that patients encounter distress and fear due to treatment immobilization and unfamiliarity with procedures respectively. Information provision is a common need raised by patients and caregivers. Patients and caregivers report relationship problems due to affected sexual functions. To facilitate future studies, solutions to each identified psychosocial need are proposed in the discussion based on the 17 selected papers and other supporting literature. This review proposes art therapy to alleviate psychological distress, and pre-treatment information sessions to reinforce information delivery. Creative interventions such as a sexual rehabilitation program are recommended. Future studies are warranted to examine the interventions and thus improve the patients’ and caregivers’ well-being.